Gravity observations at Jang Bogo Station, Antarctica, and scale factor calibrations of different relative gravimeters - Fukuda, Yoichi; Okuno, Jun'ichi; Doi, Koichiro; Lee, Choon-Ki (Polar Science, 2021)
We conducted gravity observations in Antarctica at Jang Bogo Station (JBS) during the 2019–2020 Austral summer season using an FG5-210 absolute gravimeter (AG) and a LaCoste & Romberg (LCR) Model D-58 relative gravimeter. Absolute gravity measurements were successfully made at reference gravity point JBSAG1 and newly established gravity point JBSAG2, yielding about 19,000 and 14,400 drops of data, respectively, with measurement precisions better than 0.4 μGal (1 μGal = 10−8 m s−2). In addition, relative gravity measurements were conducted at 10 other newly established gravity points, with accuracies better than 10 μGal, to supplement the absolute gravity data. Superconducting gravimeter (SG) observation with an iGrav-021 instrument has been underway at JBS since 2016. Since an SG is a relative gravimeter, the calibration of the scale factor is essential for long-term gravity monitoring. In addition, the D-58 instrument was required for scale factor calibration. To calibrate the scale factors of these gravimeters, we first estimated a value for the iGrav-021 using parallel observations with the FG5-210 instrument. The D-58 scale factor was then estimated indirectly from parallel observations with the iGrav-021. These calibrations should ensure accurate gravity monitoring in future work. journal article